Integrating Imaging - Vinall, Maria (MD Conference Express, 2010)
The integration of imaging modalities may provide a broader picture of disease anatomy, burden, and molecular activity. This article discusss the utility of magnetic resonance and computed tomography imaging in the setting of electrophysiology.